Economic Policy Uncertainty (EPU) and China's Export Fluctuation in the Post-pandemic Era: An Empirical Analysis based on the TVP-SV-VAR Model - Hu, Guoheng; Liu, Shan (Frontiers in Public Health, 2021)
In the COVID-19 pandemic, bidirectional policy adopted by the governments to stimulate domestic economy and reinforce foreign trade control is making the trade environment abnormally complex. China is facing a new challenge in export trade growth. Based on the continuous monthly data from January 2002 to April 2021, the paper uses the time-varying TVP-SV-VAR model to study the impulse response of China’s export trade to economic policy uncertainty (EPU). It is found that 1) on the whole, the shock of global EPU and China’s EPU on China’s export to the OBOR/RCEP member countries is time-varying, different and structurally significant; 2) during the pandemic, EPU has a significant short-term negative shock on China’s gross exports and export to OBOR/RCEP members, and this shock is especially big in the case of global EPU. In the post-pandemic era, China should strengthen pandemic control and economic risk monitoring, continue with execution of multilateral FTAs and create a sustainably stable export trade environment.